2022
DOI: 10.1111/ans.18190
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic findings after CT proven acute diverticulitis: a systematic review and meta‐analysis

Abstract: Background Traditionally, international guidelines recommend patients with acute diverticulitis should be followed up with a colonoscopy 6–8 weeks after discharge. However, the need for an interval colonoscopy has been increasingly challenged in the setting of computed tomography (CT). Previous meta‐analyses have included studies which combined suspected rather than imaging confirmed diverticulitis and often without correlation with endoscopic findings. This meta‐analysis aims to investigate endoscopic finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
0
0
0
Order By: Relevance
“…We found an increased risk of colon cancer in patients with complicated diverticulitis compared with uncomplicated diverticulitis in the adjusted analysis. Our results are aligned with the conclusions of two recent meta-analyses [42,46]. In our analysis, the difference in risk was only merely significant when adjusting for surgery.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found an increased risk of colon cancer in patients with complicated diverticulitis compared with uncomplicated diverticulitis in the adjusted analysis. Our results are aligned with the conclusions of two recent meta-analyses [42,46]. In our analysis, the difference in risk was only merely significant when adjusting for surgery.…”
Section: Discussionsupporting
confidence: 91%
“…We believe this to be due to a screening effect from the follow-up colonoscopy. Previous studies have found that 14-31% had adenomas upon colonoscopy after an episode of diverticulitis [41][42][43][44]. In a recently published systematic review, we also found that there was no increased long-term risk of colon cancer from six months after an episode of diverticulitis [45].…”
Section: Discussionsupporting
confidence: 68%
“…Of those diagnosed with colorectal cancer, 85% were concordant with the site of the diverticulitis on CT, while 15% were incidental findings. They recommended routine colonoscopic follow-up in convenient individuals [18]. Laurie et al conducted a retrospective analysis to compare colonoscopy versus post-computed tomography for confirmed diverticulitis.…”
Section: Discussionmentioning
confidence: 99%